Influence of social and religious factors in Polish Sejm elections, 2001–2007 - Bilska-Wodecka Elżbieta; Matykowski Roman (Bulletin of Geography. Socio-Economic Series, 2015)
The analysis presented herein addresses the issue of social and religious diversity within the Catholic Church and its influence on voter turnout and Sejm election results in Poland. The paper covers election results from 2001 to 2007. Both organizational-institutional characteristics and social-religious characteristics of the Church have been taken into account when assessing the impact of the Church on regional differences in political support for selected political factions in 2005. The impact of each factor on the support level for a given party or political orientation in a regional (spatial) context was assessed on the basis of the degree of coincidence of the factors of interest, measured using the coefficient of correlation.